A checklist of masteral and doctoral dissertations about the Philippines and/or written by Filipinos submitted to American and English universities, 1907-1972 - Villa, Norma S.; Vallejo, Rosa M.; Picache, Ursula G. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1975)
This checklist is an attempt to provide graduate students, researchers, and scholars a comprehensive listing of masteral theses and doctoral dissertations on the Philippines and/or written by Filipinos in various disciplines and submitted to American and English universitites. It has been compiled in response to the need of the Philippines to maintain bibliographic control of unpublished theses and dissertations on the subject mentioned earlier. While serving as a ready reference for students, researchers, etc., this is intended to inform graduate students of research work already done in their field thus minimizing duplication of research efforts and guiding them in the selection of their dissertation topics.
There are 1,725 masteral and doctoral dissertations submitted to American and English universities from 1907-1972. Of these entries, approximately 470 masteral and doctoral dissertations were written by foreigner while the rest were submitted by Filipinos.
The subjects covered are Agricultural Sciences, Anthropology and Sociology, Arts and Humanities, Biological Sciences, Earth Science, Economics, Education, Engineering, Geography, Language and Literature, Mathematics, Medical Sciences, Political Science, Public Administration and International Relations, Psychology, and other professional fields such as Home Economics, Law, Library Science, Mass Communication, Speech and others.
This checklist is provided with an author Index, an institutional index and a chronological index in order to facilitate the location of entries.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: Dissertations, Academic -- Bibliography. -- Great Britain; Dissertations, Academic -- Bibliography. -- Philippines; Dissertations, Academic -- Bibliography. -- United States